2021
DOI: 10.1111/ajt.16484
|View full text |Cite
|
Sign up to set email alerts
|

Follicular T cells mediate donor-specific antibody and rejection after solid organ transplantation

Abstract: Over the past 20 years, the development of newer immunosuppressive drugs has improved short-term survival after kidney transplantation. 1 However, long-term survival has not substantially improved. Long-term graft loss has been attributed to chronic antibody-mediated rejection (AbMR) caused by donorspecific antibodies (DSAs). 1,2 DSA can be preexisting or can arise

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
(39 reference statements)
4
35
0
Order By: Relevance
“…Tfh cells optimize early SARS-CoV-2-specific germinal center responses after protein vaccination The precise roles of Tfh cells in mediating clonal dynamics within GCs have remained poorly understood due to a lack of tools. We recently developed a ''Tfh-DTR'' mouse to delete Tfh cells with administration of diphtheria toxin (DT) (Mohammed et al, 2021). The Tfh-DTR contains both Cd4 Cre and Cxcr5 LoxSTOPLoxDTR alleles, which posits the DT receptor (DTR) on the surface of CD4 + T cells expressing CXCR5, including Tfh cells.…”
Section: Sars-cov-2 Spike Protein Vaccination Generates Robust Germin...mentioning
confidence: 99%
See 2 more Smart Citations
“…Tfh cells optimize early SARS-CoV-2-specific germinal center responses after protein vaccination The precise roles of Tfh cells in mediating clonal dynamics within GCs have remained poorly understood due to a lack of tools. We recently developed a ''Tfh-DTR'' mouse to delete Tfh cells with administration of diphtheria toxin (DT) (Mohammed et al, 2021). The Tfh-DTR contains both Cd4 Cre and Cxcr5 LoxSTOPLoxDTR alleles, which posits the DT receptor (DTR) on the surface of CD4 + T cells expressing CXCR5, including Tfh cells.…”
Section: Sars-cov-2 Spike Protein Vaccination Generates Robust Germin...mentioning
confidence: 99%
“…The Tfh-DTR contains both Cd4 Cre and Cxcr5 LoxSTOPLoxDTR alleles, which posits the DT receptor (DTR) on the surface of CD4 + T cells expressing CXCR5, including Tfh cells. Tfr cells will also be deleted in the Tfh-DTR mouse, but we refer to it as the Tfh-DTR for simplicity (Mohammed et al, 2021). We vaccinated control (Cd4 Cre Cxcr5 wt ) or Tfh-DTR (Cd4 Cre Cxcr5 LoxSTOPLoxDTR ) mice with the SARS-CoV-2 Spike protein vaccine, administered DT, and assessed responses on day 14.…”
Section: Sars-cov-2 Spike Protein Vaccination Generates Robust Germin...mentioning
confidence: 99%
See 1 more Smart Citation
“…We also performed allogeneic kidney transplantation in Tfr-DTR mice to assess the roles of Tfr cells in controlling AMR. Although we found that Tfr cells can limit IgG DSA using splenocyte alloantigen challenge models, we did not find substantial differences in severity of AMR during kidney transplantation when Tfr cells were deleted ( Mohammed et al, 2021 ). However, one caveat to these experiments is that a full MHC mismatch kidney transplant model was used in which rejection rapidly occurs within 3 weeks.…”
Section: T Follicular Regulatory (Tfr) Cellsmentioning
confidence: 68%
“…We recently developed a pre-clinical allogeneic kidney transplant model to assess the roles of Tfh and Tfr cells in controlling DSA and AMR. Using a Tfh-DTR model in which Tfh cells were deleted during transplantation we found that Tfh cells were essential for IgG DSA as well as AMR after kidney transplantation ( Mohammed et al, 2021 ). We also performed allogeneic kidney transplantation in Tfr-DTR mice to assess the roles of Tfr cells in controlling AMR.…”
Section: T Follicular Regulatory (Tfr) Cellsmentioning
confidence: 99%